2022
DOI: 10.1097/ta.0000000000003881
|View full text |Cite
|
Sign up to set email alerts
|

Timing is everything: Early versus late palliative care consults in trauma

Abstract: BACKGROUND:The incorporation of dedicated palliative care (PC) services in the care of the critically injured trauma patient is not yet universal. Preexisting data demonstrate both economic and clinical value of PC consults, yet patient selection and optimal timing of these consults are poorly defined, possibly leading to underutilization of PC services. Prior studies in geriatric patients have shown benefits of PC when PC clinicians are engaged earlier during hospitalization. We aim to compare hospitalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
4
1
0
Order By: Relevance
“…Both statistically and clinically significant, LOS decreased patients’ stay by half for EPC patients. This is consistent with the recent work by Spencer et al who similarly showed a decrease in the hospital and ICU LOS with EPC consultation ( 10 ), findings echoed in other studies ( 11 , 12 ). Just as important, a shorter LOS is aligned with the patient wishes of having less time within the ICU and hospital ( 13 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Both statistically and clinically significant, LOS decreased patients’ stay by half for EPC patients. This is consistent with the recent work by Spencer et al who similarly showed a decrease in the hospital and ICU LOS with EPC consultation ( 10 ), findings echoed in other studies ( 11 , 12 ). Just as important, a shorter LOS is aligned with the patient wishes of having less time within the ICU and hospital ( 13 ).…”
Section: Discussionsupporting
confidence: 93%
“…Mortality for EPC was 36%, and for LPC, it was 35% ( p = 0.473). Consistent with published work by Spencer et al ( 10 ), our findings suggest that the time of palliative care consultation had no impact on the mortality rates of the two groups. Although there was a slight trend for patients with EPC to have discharge to home, statistical significance was not reached, and there was no difference between other discharge dispositions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…hours) for trauma patients may lead to shorter length of stay, reduced ventilator days, decreased invasive procedures and lower overall costs. 9 There are, however, limited studies on the current practices and outcomes for palliative care in pediatric trauma patients, particularly those who are critically ill. Trauma remains the leading cause of morbidity and mortality in those aged 1-21 years, with traumatic brain injury (TBI) being the most common lethal injury. 10 11 Special issues pertaining to supportive care in children and adolescents include incorporation of healthcare surrogates, state rules regarding consent of minors, need for child life services, and unique challenges for bereaving families facing the loss of a child.…”
Section: Open Accessmentioning
confidence: 99%